Underlying drivers that influence farmers’ sustainable adaptation Strategies - Rulia Akhtar; Muhammad Mehedi Masud; Md. Sayed Uddin; Qazi Muhammad Adnan Hye (IDEAS, 2020)
In order to minimize the adverse effects of climate change, appropriate adaptation strategies are paramount. Farmers' socio-demographic factors play a significant role in the selection of appropriate adaptation methods. However, there is a lack of empirical evidence on how farmers’ socio-demographic factors affect the choice of specific adaptation strategies to minimize the negative effects of climate change. This study explores what the main determinants are for farmers when choosing specific adaptation strategies in the context of local climate. Data was collected using questionnaires and analyzed using statistical tools. The study found that income level, education level and experience had a positive and significant influence on farmers’ choices of climate change adaptation strategies. This implies that well-educated, wealthy, and experienced farmers are able to adapt more easily. The results also showed that farmers are aware that climate change has affected livestock and land degradation, increased food costs, and increased rural-urban migration. These negative effects of climate change on ecosystem services and agricultural production in Malaysia could be barriers to achieving sustainable agricultural practices. Therefore, the findings bring new perspectives to policymakers when developing adaptation policies for farming communities in the Malaysian agricultural sector.